Defect accumulation in β-Ga2O3 implanted with Yb - Sarwar, Mahwish; Ratajczak, Renata; Mieszczynski, Cyprian; Wierzbicka, Aleksandra; Gieraltowska, Sylwia; Heller, René; Eisenwinder, Stefan; Wozniak, Wojciech; Guziewicz, Elżbieta (Acta materialia, 2024)
Radiation-induced crystal lattice damage and its recovery in wide bandgap oxides, in particular beta-gallium oxide (β-Ga2O3), is a complex process. This paper presents the detailed study of defect accumulation in the β-Ga2O3 single crystal implanted with Ytterbium (Yb) ions and the impact of Rapid Thermal Annealing (RTA) on the defects formed. The (2¯01)oriented β-Ga2O3 single crystals were implanted with eleven fluences of Yb ions ranging from 1 × 1012 to 5 × 1015 at/cm2. Channeling Rutherford Backscattering Spectrometry (RBS/c) was used to study the crystal lattice damage induced by ion implantation and the level of structure recovery after annealing. The quantitative and qualitative analyses of collected spectra were performed by computer simulations. As a result, we present the first defect accumulation curve of β-Ga2O3 implanted with rare earth ion that reveals a two-step damage process. In the first stage, the damage of the β-Ga2O3 is inconspicuous, but begins to grow rapidly from the fluence of 1 × 1013 at/cm2, reaching the saturation at the random level for the Yb ion fluence of 1 × 1014 at/cm2. Further irradiation causes the damage peak to become bimodal, indicating that at least two new defect forms develop for the higher ion fluence. These two damage zones differently react to annealing, suggesting that they could origin from two phases, the amorphization phase and the new crystalline phase of Ga2O3. High-resolution x-ray diffraction (HRXRD) demonstrates the presence of strain and the γ phase of Ga2O3 after implantation, which disappear after annealing. [Display omitted]